Ethnomedicinal survey of some plants used for the treatment of diabetes in Ibadan, Nigeria - OS Ofuegbe (Asian Journal of Medical Sciences, 2015)
Objectives: A comprehensive survey with the aim of documenting traditional medicinal practices was carried out in targeted areas of Ibadan, Nigeria in order to inventory plants used by traditional healers in the area for the management of diabetes.